Technology adoption as survival strategy for small and medium enterprises during COVID-19 - Ashraf Mishrif; Asharul Islam Khan (Journal of Innovation and Entrepreneurship, 2023)
Globally, operational capabilities of small and medium enterprises (SMEs) have been immensely affected by the COVID-19 pandemic, forcing many companies to use technology and innovation rather than the more traditional methods of operations. As the extent to which SMEs' adoption of technological tools is still unknown, this study assesses the technological transformations and the challenges facing SMEs during the pandemic. It also evaluates the levels of customers satisfaction and future technological innovation plans in SMEs. Using quantitative and qualitative primary date, we empirically examine how COVID-19 lockdowns accelerated technology use in Omani SMEs and test eight hypotheses applying paired t test and Pearson's correlation. Although the impact of the COVID-19 pandemic has been globally felt, this study focuses on the effect of the pandemic on SMEs operating in the logistics and supply chain sector in the Sultanate of Oman. The primary data used was collected through the survey questionnaire and interviews with business owners and company executives covering the period 2020-2021. The results show strong correlations between technology use before and during COVID-19; technology use during COVID-19 and in future; and technology use before COVID-19 and in future. They also reveal that technology adoption has been a successful persistence strategy during the pandemic and that highly digitized SMEs are more likely to adopt industry 4.0 technology. The findings are expected to have practical implications for policy making by investing and developing digital infrastructure to accelerate digital transformation, while company executives appreciating the requirements and benefits of adopting innovation and technology solutions to remain competitive. We acknowledge the limitation of our study to only SMEs in the Sultanate of Oman and within a short period of time during the COVID-19 pandemic. This makes it hard to generalize our findings; hence, we recommend further research in other business sectors and countries in the post-pandemic to corroborate our findings and compare outcomes. To the best of the authors' knowledge, no research has been done on SMEs that consider technological transformation during COVID-19. The study will advance knowledge of the development and adoption of technology in SMEs, as well as their impacts on productivity and efficiency.
Keywords: 650; COVID-19; Technology adoption; Impact; Operation; Small and Medium Enterprises